Evidence of Crimean-Congo Haemorrhagic Fever Virus Occurrence in Ixodidae Ticks of Armenia - Hasmik Gevorgyan; Gohar G. Grigoryan; Hripsime A. Atoyan; Martin Rukhkyan; Astghik Hakobyan; Hovakim Zakaryan; Sargis A. Aghayan (Tehran University of Medical Sciences, 2018)
Background: Crimean-Congo hemorrhagic fever (CCHF) causes serious health problems in humans. Though ticks of the genera Hyalomma play a significant role in the CCHF transmission it was also found in 31 other thick species. Methods: Totally, 1412 ticks from 8 remote sites in Armenia during 2016 were sampled, pooled (3-5 ticks per pool) and tested for the presence of CCHFV antigen using ELISA test. Results: From 359 tick pools, 132 were CCHF virus antigen-positive. From 6 tick species, four species (Rhipicephalus sanguineus, R. annulatus, R. bursa, Hyalomma marginatum) were positive for the virus antigen and R. sanguineus was the most prevalent (37.9%). Dermacentor marginatus and Ixodes ricinus revealed no positive pools, but both revealed delectable but very low virus antigen titers. The highest infection rate (50%) was observed in R. sanguineus, whereas H. marginatus rate of infection was 1 out 17. Conclusion: For the first time in the last four decades CCHF virus antigen was detected in Ixodid ticks of Armenia. This finding substantiates the role of R. sanguineus in the disease epidemiology; however, the role of H. marginatum in the CCHF virus circulation in the country could not be excluded.